2004
DOI: 10.1038/sj.gene.6364122
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 promoter single-nucleotide polymorphisms as markers for disease susceptibility and disease severity in leprosy

Abstract: We have determined IL-10 promoter genotypes of five single-nucleotide polymorphisms (SNPs): TÀ3575A, AÀ2849G, CÀ2763A, -AÀ1082G and CÀ819T. The haplotype frequencies were defined in healthy subjects compared to leprosy patients, and analyzed for their occurrence in multi-(MB) vs paucibacillary (PB) as severe and mild forms of leprosy, respectively. Haplotypes defined by three SNP positions (À3575, À2849 and À2763) captured significant differences between controls and patients (P ¼ 0.04). The haplotype carrying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 19 publications
2
50
0
7
Order By: Relevance
“…This result was reinforced with meta-analysis, in which the SNP À819C/T was tested in association with leprosy. [13][14][15][16] The pooled sample reached a total of 2702 individuals (1355 cases and 1347 controls), including subjects belonging to three Brazilian, one Malawian and one Indian populations (total of five populations). We pooled data from papers found in the literature using key words, but also included our data that were not selected in a canonical way to compare with all selected papers for meta-analysis, but the results with or without our case-control study show basically the same: association of À819T with leprosy susceptibility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result was reinforced with meta-analysis, in which the SNP À819C/T was tested in association with leprosy. [13][14][15][16] The pooled sample reached a total of 2702 individuals (1355 cases and 1347 controls), including subjects belonging to three Brazilian, one Malawian and one Indian populations (total of five populations). We pooled data from papers found in the literature using key words, but also included our data that were not selected in a canonical way to compare with all selected papers for meta-analysis, but the results with or without our case-control study show basically the same: association of À819T with leprosy susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Santos et al 13 showed that À819T allele was associated with leprosy susceptibility. Later, extended haplotypes were studied and the combination of À3575A/À2849G/À2763C/ À1082G/À819C was associated with resistance, whereas À3575T/À2849A/À2763C/À1082G/À819T was the susceptible haplotype 14 confirming the participation of À819T as a susceptibility allele of the locus. A replication study carried out in Indians implicated a different promoter haplotype associated with leprosy susceptibility (À3575T/À2849G/À2763C/À1082A/À819T/À592A), but again À819T was associated with the disease outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study from Brazil with IL-10 extended haplotypes showed that the combination of 3575A/-2849G/-2763C/-1082G/-819C was associated with resistance, and -3575T/-2849A/-2763C/-1082G/-819T was the susceptible haplotype, confirming the participation of -819T as a susceptibility allele (19 country, for example the study carried out in the Paraná State of Brazil, where the analysis of IL10 genotypes did not show any significant differences between leprosy patients and controls (7).…”
mentioning
confidence: 79%
“…Interleukin (IL)-10 gene polymorphisms have been analyzed in several populations demonstrating the association with leprosy (15)(16)(17), however results of previous works from different populations are variable (15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%